Tecnologias inclusivas adaptadas ao ensino de física: um estudo de caso aplicado à educação profissional - SOUSA, Luisa Helena Silva de (Universidade Federal do Oeste do Pará, 2021)
The present work summarizes the Master's Thesis submitted to the Graduate Program in Physics Teaching in the National Professional Master's Course in Physics Teaching (MNPEF), as part of the requirements necessary to obtain the title of Master in Physics Teaching. Bringing reflections about the policy of professional education, inclusion and teaching of Physics. This research was developed in a schoolteacher that offers professional education in the interior of the State of Pará. The general objective was to develop materials and methods that facilitate the process of teaching/learning the knowledge of physics, to students with visual impairment, using assistive technology as an auxiliary tool. Methodology, this is an exploratory research of the case study type and qualitative. The techniques used were: Direct Observation; Institutional records; Focus Groups. The research was directed to the adequacy of pre-existing technologies, making adaptations to the context of inclusive physics teaching, in the context of professional education. As a result, the Blind Banner application was created, capable of transforming the text produced by the students, the curriculum adopted was history of science by the students, into a quick response code. And, the same application is able to perform audio description to visually impaired students, providing them with autonomy and scientific empowerment.